The Stability and Wall Structure of Cylindrical Domains in Magnetic Films - Blake, Gerard Wreferd Terence (My University, 1980)
A model is presented of a cylindrical domain ("magnetic bubble") with its wall in a uniaxially anisotropic magnetic film, and data obtained from this model's numerical implementation are analyzed.
A finite-difference, static energy minimization, micro-magnetic model [23] of an axisymmetric domain wall in a magnetic film has been further developed in its physical formulation and numerical techniques. The various contributions to total energy calculated from the resulting magnetic configuration have been applied to the determination of average domain radius by means of an energy-minimization domain model developed for the purpose. The domain radius was needed to complete the wall-model algorithm and to allow it to converge to an accurate solution. This thesis describes the two aspects of this theoretical analysis, the wall model and the domain model, and the interaction between them.
The entire algorithm has been used to model magnetic bubbles in systematic surveys of applied magnetic fields and of film material parameters, namely saturation magnetization Ms, normalized anisotropy constant Q, and normalized wall energy density of bulk material, λ. Structural features of the resulting wall magnetic configurations are displayed. A comprehensive selection of features are quantified and their dependence on domain radius and on material parameters are presented and their physical explanations are discussed. Domain stability properties are derived from the theoretical model and their dependence on material paramters is analyzed.
Keywords: Physics; Physics